Co-benefits, contradictions, and multi-level governance of low-carbon experimentation: Leveraging solar energy for sustainable development in China. (November 2019) - Lo, Kevin; Castán Broto, Vanesa
Highlights: China adopts a state-led and coordinated approach to low-carbon experimentation. The approach requires dynamic mechanisms that enable the adaptation of national-level models to specific locations. The approach also requires the incorporation of local implementation lessons in national policymaking. Contradictions emerge from central-local interactions. The contradictions embedded in low-carbon policies are the engines that drive action and change. Abstract: Experimentation has emerged as an important strategy of climate governance, and China, with a distinctive experiment-based policy process, is a leading example of a state-led and coordinated approach to low-carbon experimentation. Through a case study of the photovoltaics poverty alleviation (PVPA) initiative—an ambitious and experimental programme that explores the synergy between renewable energy and sustainable development by using photovoltaics to generate income for impoverished households and communities—this paper critically examines this top-down mode of experimentation from a multi-level perspective based on Heilmann's experimentation under hierarchy framework. Drawing from empirical evidence collected over two years from a PVPA pilot, we show that China's multi-level approach to experimentation requires dynamic mechanisms that enable not only the adaptation of national-level models to specific locations but also the incorporation of local implementation lessons in national policymaking. The resulting experimental governance thus extends from a combination of top-down mechanisms of control, local responses, and the broader contradictions that emerge from their interactions.